2003
DOI: 10.1086/345928
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneities in the Microwave Background Radiation Interpreted within the Framework of the Quasi–Steady State Cosmology

Abstract: We calculate the expected angular power spectrum of the temperature fluctuations in the microwave background radiation (MBR) generated in the quasi-steady state cosmology (QSSC). The paper begins with a brief description of how the background is produced and thermalized in the QSSC. We then discuss within the framework of a simple model, the likely sources of fluctuations in the background due to astrophysical and cosmological causes. Power spectrum peaks at l ≈ 6 − 10, 180 − 220 and 600 − 900 are shown to be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 23 publications
1
67
0
Order By: Relevance
“…In a separate paper (Narlikar et al 2002) devoted to the spectrum and fluctuations of the microwave background radiation (MBR) in the QSSC, we have shown that the MBR anisotropy from rich clusters can be revealed by a peak in the power spectrum around , while smaller peaks are l p 200 revealed in the range from groups of galaxies and l ∼ 600-900 perhaps weaker peaks at from individual galaxies or l տ 3000 compact groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate paper (Narlikar et al 2002) devoted to the spectrum and fluctuations of the microwave background radiation (MBR) in the QSSC, we have shown that the MBR anisotropy from rich clusters can be revealed by a peak in the power spectrum around , while smaller peaks are l p 200 revealed in the range from groups of galaxies and l ∼ 600-900 perhaps weaker peaks at from individual galaxies or l տ 3000 compact groups.…”
Section: Discussionmentioning
confidence: 99%
“…In adherence to the Perfect Cosmological Principle, a creation field (C-field) was for the first time introduced [39] to reconcile with homogeneous density by creation of new matter in the voids caused by the expansion of the universe. It was further refined and reformulated in the Hoyle and Narlikar theory of gravitation [40], see Refs [41,42,43,44] for details of the C-field cosmology. The C-field appeared on the right hand side of the Einstein equation.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that inhomogeneities on the observed scale result from the thermalized radiation from clusters, groups of galaxies etc. thermalized at the minimum of the last oscillation (Narlikar et al, 2003). By using a toy model for these sources, it has been shown that the resulting angular power spectrum has a satisfactory fit to the data compiled by Podariu et al (2001) for the band power spectrum of the CMBR temperature inhomogeneities.…”
Section: The Radiation Backgroundmentioning
confidence: 91%
“…This set of parameters has been used in recent papers on the QSSC (Narlikar, et al 2002(Narlikar, et al , 2003. For this model the ratio of maximum to minimum scale factor in any oscillation is around 9.6.…”
Section: Cosmological Parametersmentioning
confidence: 99%
See 1 more Smart Citation